Dissecting the role of cancer‐associated fibroblast‐derived biglycan as a potential therapeutic target in immunotherapy resistance: A tumor bulk and single‐cell transcriptomic study. Issue 2 (11th February 2023) - Zheng, Shaoquan; Liang, Jie‐Ying; Tang, Yuhui; Xie, Jindong; Zou, Yutian; Yang, Anli; Shao, Nan; Kuang, Xiaying; Ji, Fei; Liu, Xuefeng; Tian, Wenwen; Xiao, Weikai; et al.
Abstract: Introduction: Cancer‐associated fibroblasts (CAFs) are correlated with the immunotherapy response. However, the culprits that link CAFs to immunotherapy resistance are still rarely investigated in real‐world studies. Objectives: This study aims to systematically assess the landscape of fibroblasts in cancer patients by combining single‐cell and bulk profiling data from pan‐cancer cohorts. We further sought to decipher the expression, survival predictive value and association with immunotherapy response of biglycan (BGN), a proteoglycan in the extracellular matrix, in multiple cohorts. Methods: Pan‐cancer tumor bulks and 27 single‐cell RNA sequencing cohorts were enrolled to investigate the correlations and crosstalk between CAFs and tumor or immune cells. Specific secreting factors of CAFs were then identified by expression profiling at tissue microdissection, isolated primary fibroblasts and single‐cell level. The role of BGN was further dissected in additional three bulk and five single‐cell profiling datasets from immunotherapy cohorts and validated in real‐world patients who have received PD‐1 blockade using immunohistochemistry and immunofluorescence. Results: CAFs were closely correlated with immune components. Frequent crosstalk between CAFs and other cells was revealed by the CellChat analysis. Single‐cell regulatory network inference and clustering identified common and distinct regulators for CAFs across cancers. The BGN was determined to be a specific secreting factor of CAFs. The BGN served as an unfavourable indicator for overall survival and immunotherapy response. In the real‐world immunotherapy cohort, patients with high BGN levels presented a higher proportion of poor response compared with those with low BGN (46.7% vs. 11.8%) and a lower level of infiltrating CD8+ T cells was also observed. Conclusions: We highlighted the importance of CAFs in the tumor microenvironment and revealed that the BGN, which is mainly derived from CAFs, may be applicable in clinical practice and serve as a therapeutic target in immunotherapy resistance. Abstract : There are tight correlations between CAFs and immune cells in pan‐cancer bulk cohort. Single‐cell data reveals regulators for CAFs and frequent crosstalk with other cells. In various cancers, stromal biglycan is dominantly derived from CAFs. Biglycan is an unfavourable indicator for survival and immunotherapy response in cancer.